The Intimate Critique : Autobiographical Literary Criticism - Zauhar, Frances Murphy; Frey, Olivia; Freedman, Diane P. (Book collections on Project MUSE., 1993)
For a long time now, readers and scholars have strained against the limits of traditional literary criticism, whose precepts--above all, "objectivity"--Seem to have so little to do with the highly personal and deeply felt experience of literature. The Intimate Critique marks a movement away from this tradition. With their rich spectrum of personal and passionate voices, these essays challenge and ultimately breach the boundaries between criticism and narrative, experience and expression, literature and life. Grounded in feminism and connected to the race, class, and gender paradigms in cultural studies, the twenty-six contributors to this volume--including Jane Tompkins, Henry Louis Gates, Jr., Shirley Nelson Garner, and Shirley Goek-Lin Lim--respond in new, refreshing ways to literary subjects ranging from Homer to Freud, Middlemarch to The Woman Warrior, Shiva Naipaul to Frederick Douglass. Revealing the beliefs and formative life experiences that inform their essays, these writers characteristically recount the process by which their opinions took shape--a process as conducive to self-discovery as it is to critical insight. The result--which has been referred to as "personal writing," "experimental critical writing," or "intellectual autobiography"--maps a dramatic change in the direction of literary criticism. Contributors. Julia Balen, Dana Beckelman, Ellen Brown, Sandra M. Brown, Rosanne Kanhai-Brunton, Suzanne Bunkers, Peter Carlton, Brenda Daly, Victoria Ekanger, Diane P. Freedman, Olivia Frey, Shirley Nelson Garner, Henry Louis Gates, Jr., Melody Graulich, Gail Griffin, Dolan Hubbard, Kendall, Susan Koppelman, Shirley Geok-Lin Lim, Linda Robertson, Carol Taylor, Jane Tompkins, Cheryl Torsney, Trace Yamamoto, Frances Murphy Zauhar